2022
DOI: 10.3390/catal12080812
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorine Modification of Precipitated Iron Catalysts on Their Fischer–Tropsch Synthesis Properties

Abstract: Precipitated iron Fischer–Tropsch synthesis catalysts impregnated with chlorine were prepared and their Fischer–Tropsch synthesis performances were tested in a 1 L stirred tank reactor. The results showed that the chlorine modification had a significant influence on the Fischer–Tropsch synthesis performance of the precipitated iron catalyst. Compared with the catalyst without the chlorine modification, the catalyst containing about 0.1 wt% chlorine was deactivated by about 40% and the catalyst containing about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The synergistic effect between FeC x and FeO x also plays an important role in the CO 2 –FTS performance. Iron oxides have proven to be inert for FTS process, but providing abundant oxygen vacancy sites for CO 2 adsorption and activation. , Lu et al investigated CO 2 hydrogenation to olefins and ethanol over Na-promoted Fe 3 O 4 microspheres under different operating pressures (0.5 MPa, 3.0 MPa). It is proposed that CO 2 activation at the carbide/oxide interface is the key to tune the reaction pathway and product selectivity.…”
Section: Active Phases In Co X Hydrogenation Over Fe-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synergistic effect between FeC x and FeO x also plays an important role in the CO 2 –FTS performance. Iron oxides have proven to be inert for FTS process, but providing abundant oxygen vacancy sites for CO 2 adsorption and activation. , Lu et al investigated CO 2 hydrogenation to olefins and ethanol over Na-promoted Fe 3 O 4 microspheres under different operating pressures (0.5 MPa, 3.0 MPa). It is proposed that CO 2 activation at the carbide/oxide interface is the key to tune the reaction pathway and product selectivity.…”
Section: Active Phases In Co X Hydrogenation Over Fe-based Catalystsmentioning
confidence: 99%
“…In contrast to alkali metals, Fe species can form electron-deficient structures under the influence of such additives . S and Cl are generally considered poisonous to active phase . However, some studies have shown that the introduction of Cl promoter through different precursors can promote high selectivity toward light olefins.…”
Section: Steering the Structural Evolution: The Role Of Catalyst Designmentioning
confidence: 99%
See 1 more Smart Citation